(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: This study assesses the clinical efficacy of utilizing a custom-manufactured articulating antibiotic-loaded cement spacer in the management of periprosthetic joint infections (PJI), as observed in cases treated at the Ho Chi Minh City Orthopedic Trauma Hospital from 2022 to 2024. Methods: A case series involving four patients with confirmed PJI, including two cases of prosthetic knee infection and two cases involving hip prosthesis infections, were managed with an articulating antibiotic-impregnated cement spacer. This approach aimed to maintain joint functionality while enabling eradication of infection prior to second-stage reimplantation. Outcomes were compared to those associated with static spacers that lack articulating functionality. Results: All patients demonstrated favorable clinical outcomes, with effective infection resolution and absence of severe complications over the observation period. Enhanced postoperative range of motion and overall improvement in quality of life were documented, with rapid analgesic response and early ambulation. Conclusion: The application of a custom-manufactured articulating antibiotic-loaded cement spacer is a feasible, cost-effective, and clinically advantageous intervention for PJI management. It provides effective infection control while preserving joint mobility, thereby optimizing conditions for successful reimplantation in a two-stage revision arthroplasty. This approach is especially beneficial for resource-limited healthcare settings.